Modelling of cultural ecosystem services through social media photos: The case of Eskişehir - E. Seda ARSLAN; Ömer K. ÖRÜCÜ (Turkish Journal of Forestry, 2020)
Natural and cultural landscapes contain many ecosystems that produce natural and cultural values in different geographies of the earth. Recently, ecosystem services have been handled by researchers from different disciplines, which generally could be explained as benefits from ecosystems. The mapping of these benefits and services produced by numerous ecosystems around the world provides an opportunity to express not only ecosystem potential and environmental factors associated with it, but also it is a very effective way of spatial expression of ecosystem services. In this research, social media photographs were used to model the spatial distribution of cultural ecosystem services. In the study carried out in Eskişehir province, geographically marked photographs tagged with the name Eskişehir in Flickr application on social media were evaluated and associated with environmental variables. ArcGIS as software based on geographical information system and MaxEnt is based on maximum entropy were integrated to each other for modelling cultural ecosystem services. According to this; land cover and land use are associated with roads, streams, cultural and natural landscape characteristics and have been modelled by combining landscape potential and user preferences (cultural ecosystem service potential). The statistical findings of the study receiver operating characteristic (ROC) and Jackknife graphs prove the reliability of the model. As a result; it is thought that the data obtained from this study may help to model future scenarios based on cultural ecosystem services and to make decisions about planning and management of tourism or protected areas.